Prevalence of hazardous alcohol use among Spanish primary care providers - Esperanza Romero-Rodríguez; Luis Ángel Pérula de Torres; Juan Manuel Parras Rejano; Fernando Leiva-Cepas; Francisco Camarelles Guillem; Rodrigo Fernández Márquez; José Ángel Fernández García; Collaborative Group Alco-AP (BMC Family Practice, 2019)
Abstract Background Alcohol use by health care professionals is one of the potential factors that may affect the prevention of hazardous drinking in Primary Care (PC). The objective of the study was to estimate the prevalence of hazardous alcohol use by PC professionals and assess the existing relationship between socio-demographic and occupational variables of PC professionals and their alcohol use. Methods A descriptive, cross-sectional, observational, multicenter study was performed. Location: PC sites of the Spanish National Health Care System (NHS). Participants: Physicians and nurses, who completed an online questionnaire intended to identify the pattern of hazardous alcohol use through the AUDIT-C test. The study population was recruited through random sampling stratified by regions of the PC sites in the NHS. The primary measurements: Frequency of alcohol use, number of drinks containing alcohol on a typical day, frequency of six or more drinks on one occasion. Results One thousand seven hundred sixty professionals completed the questionnaire. Hazardous alcohol use was detected in 27.80% (95% CI: 25.5–29.7) of PC providers. The prevalence of hazardous alcohol use was higher in males (34.2%) [95% CI: 30.4–37.6] and professionals aged 56 years or over (34.2%) [95% CI: 28.2–40.2]. The multiple logistic regression analysis revealed a higher hazardous use in males (OR = 1.52; 95% CI: 1.22–1.90), PC physicians (OR = 1.42; 95% CI: 1.01–2.02) and professionals with more time worked (OR = 1.03; 95% CI: 1.01–1.05). Conclusion Our study shows the current prevalence of hazardous alcohol use among Spanish PC providers, revealing a higher percentage of hazardous alcohol use in healthcare professionals compared to the Spanish general population. Further interventions are required to increase the awareness of negative consequences derived from alcohol use among PC professionals and its impact on the clinical setting.